2022
DOI: 10.3390/microorganisms10010178
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic Lockdown on Pediatric Infections—A Single-Center Retrospective Study

Abstract: Since the SARS-CoV-2 outbreak, many countries have introduced measures to limit the transmission. The data based on ICD-10 codes of lower respiratory tract infections and microbiological analysis of respiratory and gastrointestinal infections were collected. The retrospective five-year analysis of the medical records revealed a substantial decrease in respiratory tract infections during the pandemic year (from April 2020 to March 2021). We noted an 81% decline in the LRTI-associated hospital admissions based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 12 publications
7
22
0
1
Order By: Relevance
“…Similar data were reported by Grochowska et al, who focused on changes in the occurrence of transmissible viral infections in children [10]. Their microbiological analysis (until April 2021) documented 87% fewer rotavirus infections and 47% norovirus infections during the pandemic.…”
Section: Discussionsupporting
confidence: 82%
“…Similar data were reported by Grochowska et al, who focused on changes in the occurrence of transmissible viral infections in children [10]. Their microbiological analysis (until April 2021) documented 87% fewer rotavirus infections and 47% norovirus infections during the pandemic.…”
Section: Discussionsupporting
confidence: 82%
“…A multicenter surveillance study conducted with hospitalized pediatric patients in Japan observed a markedly reduction in enteric viruses detection, with a decrease in HAdV detection rate of 13.5% during the COVID-19 pandemic 49 . Other studies have also reported the decline in the incidence of several pediatric infectious diseases of viral etiology during the COVID-19 pandemic, including gastroenteric viruses 50 53 .…”
Section: Discussionmentioning
confidence: 94%
“…It is reported that among children infected with community-acquired pneumonia in Shanghai, China, the detection rate of eight of the most common respiratory viruses, which ranged from 16.9% to 26.9% during 2011 to 2019, dramatically decreased to 10.5% in 2020( Li et al, 2022 ). Another microbiological study in Poland discovered a 99% drop in the respiratory syncytial virus among pediatric infections during the pandemic season until April 2021, compared to the pre-pandemic years( Grochowska et al, 2022 ). In addition, many studies also noticed the change in the incidence of bacterial pneumonia during the COVID-19 pandemic( Amin-Chowdhury et al, 2021 , Brueggemann et al, 2021 , Chan et al, 2021 , Chao and Lai, 2022 , Danino et al, 2021 , Fujita, 2021 , Zhang et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%